Cable waterproof insulation material and preparation method thereof

By mixing polyethylene and other high -performance materials and conducting high -energy electron beam splits, the problem of tightness and waterproof effects of cable insulation materials is solved, and high -strength, waterproof, flame retardant and abrasion -resistant cables are realized. Insulation.

CN119350747AInactive Publication Date: 2025-01-24YANGZHOU MEIHENG CABLE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411547705.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of cables, in particular to a cable waterproof insulating material and a preparation method thereof. The invention provides a preparation method of a cable waterproof insulation material, which comprises the following steps: synthesizing hexa (4-allylphenoxy) cyclotriphosphazene by using 4-allylphenol and hexachlorocyclotriphosphazene as raw materials; then, hexamethylcyclotrisiloxane, n-butyllithium and dimethylchlorosilane are subjected to a reaction, and single-ended active hydrogen polydimethylsiloxane is obtained; and finally, carrying out a reaction on the hexa (4-allylphenoxy) cyclotriphosphazene and the single-ended active hydrogen polydimethylsiloxane, so as to obtain the polysiloxane grafted cyclotriphosphazene. Polyethylene is selected as a base material and is subjected to melt blending with an ethylene-vinyl acetate copolymer, polyethylene grafted glycidyl methacrylate, polysiloxane grafted cyclotriphosphazene, magnesium hydroxide and calcium carbonate, and then a hot press molding process and high-energy electron beam irradiation are performed to obtain the waterproof, flame-retardant, wear-resistant and high-strength cable insulation material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable preparation, and in particular to a cable waterproof insulating material and a preparation method thereof. Background Art

[0002] Cable is a general term for optical cables, electrical cables and other items. Cables are very common and indispensable tools in daily life, mainly used for control installation, connecting equipment, transmitting electricity, etc. Insulation material is an important material set on the outside of the cable to protect the cable from external factors such as environment, climate, rain, etc., usually made of polymer resin material.

[0003] At present, insulating materials generally use a single polymer resin material such as polyethylene, polyvinyl chloride, polypropylene, etc. as the main material. In practical applications, inorganic fillers are usually added as flame retardants and directly blended with the main resin. However, due to the high surface energy of inorganic fillers, direct blending with polymer resins will result in poor dispersion and easy agglomeration, resulting in poor density of the insulating material and greatly reduced waterproof effect. In addition, considering the use scenarios of cables, it is also crucial to improve the strength, toughness and wear resistance of the insulating material. Therefore, it is very necessary to modify based on the existing technology and provide a method for preparing waterproof insulating materials for cables. Summary of the invention

[0004] The object of the present invention is to provide a cable waterproof insulation material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a cable waterproof insulation material and a preparation method thereof, comprising the following steps: Step 1: S11: Disperse 4-allylphenol in acetone, stir magnetically under nitrogen atmosphere, add sodium hydroxide and catalyst tetrabutylammonium bromide, heat to 40-45°C, react for 3-4h, add a mixture of hexachlorocyclotriphosphazene and acetone, react at 50-55°C for 60-72h, and remove acetone by rotary evaporation; add dichloromethane to the crude product, wash with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, remove dichloromethane by rotary evaporation, add ethanol for ultrasonic precipitation, filter and recrystallize with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene; S12: Disperse hexamethylcyclotrisiloxane in toluene, use n-butyl lithium as an anion initiator and tetrahydrofuran as a promoter, perform polymerization at 40-50°C for 6-12 hours, add dimethylchlorosilane for end-capping, filter, and remove low-boiling substances by reduced pressure distillation to obtain single-terminal active hydrogen polydimethylsiloxane; S13: Disperse hexa(4-allylphenoxy)cyclotriphosphazene in toluene, use an isopropanol solution of chloroplatinic acid as a catalyst, heat to 100-105°C in a nitrogen environment, add single-terminal active hydrogen polydimethylsiloxane after the system temperature stabilizes, react for 10-12 hours, cool and remove impurities by vacuum distillation to obtain polysiloxane-grafted cyclotriphosphazene; Step 2: Polyethylene, ethylene-vinyl acetate copolymer, polyethylene grafted glycidyl methacrylate, polysiloxane grafted cyclotriphosphazene, magnesium hydroxide and calcium carbonate are melt-blended; the melt-blended materials are put into a mold, hot-pressed and then irradiated with a high-energy electron beam to obtain a cable waterproof insulation material.

[0006] Furthermore, in S11, the reaction is carried out at a molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene of 6:6:1.

[0007] Furthermore, in S12, the molar ratio of hexamethylcyclotrisiloxane, n-butyllithium and dimethylchlorosilane is (5-8):1:1.

[0008] Furthermore, in S13, hexa(4-allylphenoxy)cyclotriphosphazene reacts with single-terminal active hydrogen polydimethylsiloxane at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 6:(1-2).

[0009] Furthermore, in step 2, the content of each component, calculated by weight, is 100 parts of polyethylene, 10 to 25 parts of ethylene-vinyl acetate copolymer, 12 to 17 parts of polyethylene grafted glycidyl methacrylate, 8 to 15 parts of polysiloxane grafted cyclotriphosphazene, 50 to 80 parts of magnesium hydroxide, and 50 to 80 parts of calcium carbonate.

[0010] Furthermore, the melt blending temperature is 125-140° C.; the hot pressing molding temperature is 125-135° C. and the pressure is 3-3.5 MPa; and the high energy electron beam irradiation dose is 150-170 kGy.

[0011] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a method for preparing waterproof insulation materials for cables. When preparing the waterproof insulation materials, polyethylene is selected as a substrate, and it is melt-blended with ethylene-vinyl acetate copolymer, polyethylene grafted glycidyl methacrylate, polysiloxane grafted cyclotriphosphazene, magnesium hydroxide, and calcium carbonate, and then subjected to a hot pressing molding process and high-energy electron beam irradiation to obtain a waterproof, flame-retardant, wear-resistant, high-strength finished product. Among them, polyethylene grafted glycidyl methacrylate contains epoxy groups. During melt blending, the reaction activity of the epoxy groups can be used to combine with the hydroxyl groups on the surface of the inorganic filler, thereby performing a modification treatment and improving the compatibility between the inorganic filler and the polymer matrix. In the present invention, polysiloxane grafted cyclotriphosphazene, as a flame-retardant polymer, can be synergistically modified with the inorganic flame retardant magnesium hydroxide to jointly improve the flame retardant properties of the material.

[0012] When preparing polysiloxane grafted cyclotriphosphazene, the present invention first uses 4-allylphenol and hexachlorocyclotriphosphazene as raw materials to synthesize hexa(4-allylphenoxy)cyclotriphosphazene; then hexamethylcyclotrisiloxane, n-butyl lithium and dimethylchlorosilane are reacted to prepare single-end active hydrogen polydimethylsiloxane; through a hydrosilylation reaction, the silicon-hydrogen bond on the single-end active hydrogen polydimethylsiloxane reacts with the allyl group of hexa(4-allylphenoxy)cyclotriphosphazene to obtain polysiloxane grafted cyclotriphosphazene. The polysiloxane grafted cyclotriphosphazene contains C, N and P and has good flame retardant properties. The organosilicon in the polysiloxane chain segment generates molten droplets when burning, and generates a dense and stable silicon-containing (mainly silicon dioxide) carbon layer on the surface of the polymer substrate, thereby also playing a role of heat insulation and oxygen isolation, further improving the flame retardant effect. The addition of polysiloxane can also improve the melt fluidity, make the material surface smoother and more hydrophobic, and improve the waterproof performance; in addition, it can also improve the scratch resistance and improve the toughness and strength of the material. By utilizing the allyl groups on hexa(4-allylphenoxy)cyclotriphosphazene that do not participate in the hydrosilylation reaction and irradiating with high-energy electron beams, the polysiloxane-grafted cyclotriphosphazene is cross-linked with the polyethylene matrix to further improve the performance of the material.

[0013] It should be noted that compared with hexa(4-allylphenoxy)cyclotriphosphazene, due to the larger molecular weight of the polysiloxane chain, the steric hindrance effect is obvious, and the polysiloxane-grafted cyclotriphosphazene is not easy to agglomerate in the polymer matrix and has better dispersibility; however, when the grafting amount is too high, the larger steric hindrance will hinder the subsequent cross-linking reaction, thereby affecting the performance of the material. After multiple experiments by the R&D personnel, it was found that during the grafting, the hexa(4-allylphenoxy)cyclotriphosphazene and the single-terminal active hydrogen polydimethylsiloxane were controlled to react at a carbon-carbon double bond to silicon-hydrogen bond molar ratio of 6: (1~2), and the obtained polysiloxane-grafted cyclotriphosphazene had the best modification effect on the insulating material. DETAILED DESCRIPTION

[0014] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0015] Materials and sources used in the present invention: Polyethylene (FB9500, relative molecular mass: 150×10 3 ~250×10 3 ), ethylene-vinyl acetate copolymer (EA19400) came from LG Co., Ltd. of South Korea; magnesium hydroxide (HS-02) came from Dalian Yatai Science and Technology New Materials Co., Ltd.; calcium carbonate (WN506) came from Changzhou Calcium Carbonate Co., Ltd.; polyethylene grafted glycidyl methacrylate (CMG5904) came from Jiayirong Polymer (Shanghai) Co., Ltd.

[0016] Embodiment 1: A waterproof cable insulation material and a preparation method thereof, comprising the following steps: Step 1: S11: Disperse 4-allylphenol in acetone, stir magnetically under nitrogen atmosphere, add sodium hydroxide and catalyst tetrabutylammonium bromide, heat to 40°C, react for 3h, add a mixture of hexachlorocyclotriphosphazene and acetone, react at 50°C for 60h, and remove acetone by rotary evaporation; add dichloromethane to the crude product, wash with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, remove dichloromethane by rotary evaporation, add ethanol for ultrasonic precipitation, filter and recrystallize with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene; wherein the molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene is 6:6:1 for reaction; S12: Disperse hexamethylcyclotrisiloxane in toluene, use n-butyl lithium as an anion initiator and tetrahydrofuran as a promoter, perform polymerization reaction at 40° C. for 6 hours, add dimethylchlorosilane for end-capping, filter, and remove low-boiling substances by reduced pressure distillation to obtain single-terminal active hydrogen polydimethylsiloxane; wherein the molar ratio of hexamethylcyclotrisiloxane, n-butyl lithium, and dimethylchlorosilane is 8:1:1; S13: Disperse hexa(4-allylphenoxy)cyclotriphosphazene in toluene, use an isopropanol solution of chloroplatinic acid as a catalyst, heat to 100°C in a nitrogen environment, add single-end active hydrogen polydimethylsiloxane after the system temperature stabilizes, react for 10 hours, cool and remove impurities by reduced pressure distillation to obtain polysiloxane-grafted cyclotriphosphazene; wherein hexa(4-allylphenoxy)cyclotriphosphazene and single-end active hydrogen polydimethylsiloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 6:1; Step 2: 100kg of polyethylene, 18kg of ethylene-vinyl acetate copolymer, 12kg of polyethylene grafted glycidyl methacrylate, 15kg of polysiloxane grafted cyclotriphosphazene, 75kg of magnesium hydroxide and 75kg of calcium carbonate are mixed and melt-blended at 125°C; the melt-blended material is put into a mold, hot-pressed at 125°C and 3MPa, and irradiated with a high-energy electron beam at a dose of 170kGy; and a cable waterproof insulation material is obtained.

[0017] Embodiment 2: A waterproof cable insulation material and a preparation method thereof, comprising the following steps: Step 1: S11: Disperse 4-allylphenol in acetone, stir magnetically under nitrogen atmosphere, add sodium hydroxide and catalyst tetrabutylammonium bromide, heat to 45°C, react for 3.5h, then add a mixture of hexachlorocyclotriphosphazene and acetone, react at 50°C for 66h, and remove acetone by rotary evaporation; add dichloromethane to the crude product, wash with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, remove dichloromethane by rotary evaporation, add ethanol for ultrasonic precipitation, filter and recrystallize with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene; wherein the molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene is 6:6:1 for reaction; S12: Disperse hexamethylcyclotrisiloxane in toluene, use n-butyl lithium as an anion initiator and tetrahydrofuran as a promoter, perform polymerization reaction at 55° C. for 9 hours, add dimethylchlorosilane for end-capping, filter, and remove low-boiling substances by reduced pressure distillation to obtain single-terminal active hydrogen polydimethylsiloxane; wherein the molar ratio of hexamethylcyclotrisiloxane, n-butyl lithium, and dimethylchlorosilane is 8:1:1; S13: Disperse hexa(4-allylphenoxy)cyclotriphosphazene in toluene, use an isopropanol solution of chloroplatinic acid as a catalyst, heat to 100°C in a nitrogen environment, add single-end active hydrogen polydimethylsiloxane after the system temperature stabilizes, react for 10 hours, cool and remove impurities by reduced pressure distillation to obtain polysiloxane-grafted cyclotriphosphazene; wherein hexa(4-allylphenoxy)cyclotriphosphazene and single-end active hydrogen polydimethylsiloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 6:1.5; Step 2: 100kg of polyethylene, 18kg of ethylene-vinyl acetate copolymer, 12kg of polyethylene grafted glycidyl methacrylate, 15kg of polysiloxane grafted cyclotriphosphazene, 75kg of magnesium hydroxide and 75kg of calcium carbonate are mixed and melt-blended at 130°C; the melt-blended material is put into a mold, hot-pressed at 130°C and 3MPa, and irradiated with a high-energy electron beam at a dose of 170kGy; and a cable waterproof insulation material is obtained.

[0018] Embodiment 3: A waterproof cable insulation material and a preparation method thereof, comprising the following steps: Step 1: S11: Disperse 4-allylphenol in acetone, stir magnetically under nitrogen atmosphere, add sodium hydroxide and catalyst tetrabutylammonium bromide, heat to 45°C, react for 4h, add a mixture of hexachlorocyclotriphosphazene and acetone, react at 55°C for 72h, and remove acetone by rotary evaporation; add dichloromethane to the crude product, wash with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, remove dichloromethane by rotary evaporation, add ethanol for ultrasonic precipitation, filter and recrystallize with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene; wherein the molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene is 6:6:1 for reaction; S12: Disperse hexamethylcyclotrisiloxane in toluene, use n-butyl lithium as an anion initiator and tetrahydrofuran as a promoter, perform polymerization reaction at 50° C. for 12 hours, add dimethylchlorosilane for end-capping, filter, and remove low-boiling substances by reduced pressure distillation to obtain single-terminal active hydrogen polydimethylsiloxane; wherein the molar ratio of hexamethylcyclotrisiloxane, n-butyl lithium, and dimethylchlorosilane is 8:1:1; S13: Disperse hexa(4-allylphenoxy)cyclotriphosphazene in toluene, use an isopropanol solution of chloroplatinic acid as a catalyst, heat to 105°C in a nitrogen environment, add single-end active hydrogen polydimethylsiloxane after the system temperature stabilizes, react for 12 hours, cool and remove impurities by reduced pressure distillation to obtain polysiloxane-grafted cyclotriphosphazene; wherein hexa(4-allylphenoxy)cyclotriphosphazene and single-end active hydrogen polydimethylsiloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 6:2; Step 2: 100kg of polyethylene, 18kg of ethylene-vinyl acetate copolymer, 12kg of polyethylene grafted glycidyl methacrylate, 15kg of polysiloxane grafted cyclotriphosphazene, 75kg of magnesium hydroxide and 75kg of calcium carbonate are mixed and melt-blended at 140°C; the melt-blended material is put into a mold, hot-pressed at 135°C and 3.5MPa, and irradiated with a high-energy electron beam at a dose of 170kGy; and a cable waterproof insulation material is obtained.

[0019] Comparative Example 1: No polysiloxane-grafted cyclotriphosphazene was added, and the other parameters were the same as those in Example 1.

[0020] 100kg of polyethylene, 18kg of ethylene-vinyl acetate copolymer, 12kg of polyethylene grafted glycidyl methacrylate, 75kg of magnesium hydroxide and 75kg of calcium carbonate are mixed and melt-blended at 125°C; the melt-blended material is put into a mold, hot-pressed at 125°C and 3MPa, and irradiated with a high-energy electron beam at a dose of 170kGy; and a cable waterproof insulation material is obtained.

[0021] Comparative Example 2: Hexa(4-allylphenoxy)cyclotriphosphazene was used instead of polysiloxane to graft cyclotriphosphazene, and the other parameters were the same as those in Example 2.

[0022] Step 1: Disperse 4-allylphenol in acetone, stir magnetically under nitrogen atmosphere, add sodium hydroxide and catalyst tetrabutylammonium bromide, heat to 45°C, react for 3.5h, then add a mixture of hexachlorocyclotriphosphazene and acetone, react at 50°C for 66h, and remove acetone by rotary evaporation; add dichloromethane to the crude product, wash with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, remove dichloromethane by rotary evaporation, add ethanol for ultrasonic precipitation, filter and recrystallize with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene; wherein the molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene is 6:6:1 for reaction; Step 2: 100kg of polyethylene, 18kg of ethylene-vinyl acetate copolymer, 12kg of polyethylene grafted glycidyl methacrylate, 15kg of hexa(4-allylphenoxy)cyclotriphosphazene, 75kg of magnesium hydroxide and 75kg of calcium carbonate were mixed and melt-blended at 130°C; the melt-blended material was put into a mold, hot-pressed at 130°C and 3MPa, and irradiated with a high-energy electron beam at a dose of 170kGy; and a cable waterproof insulation material was obtained.

[0023] Comparative Example 3: The grafting amount of polysiloxane in the polysiloxane-grafted cyclotriphosphazene was increased, and the other parameters were the same as those in Example 3.

[0024] Step 1: S11: Disperse 4-allylphenol in acetone, stir magnetically under nitrogen atmosphere, add sodium hydroxide and catalyst tetrabutylammonium bromide, heat to 45°C, react for 4h, add a mixture of hexachlorocyclotriphosphazene and acetone, react at 55°C for 72h, and remove acetone by rotary evaporation; add dichloromethane to the crude product, wash with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, remove dichloromethane by rotary evaporation, add ethanol for ultrasonic precipitation, filter and recrystallize with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene; wherein the molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene is 6:6:1 for reaction; S12: Disperse hexamethylcyclotrisiloxane in toluene, use n-butyl lithium as an anion initiator and tetrahydrofuran as a promoter, perform polymerization reaction at 50° C. for 12 hours, add dimethylchlorosilane for end-capping, filter, and remove low-boiling substances by reduced pressure distillation to obtain single-terminal active hydrogen polydimethylsiloxane; wherein the molar ratio of hexamethylcyclotrisiloxane, n-butyl lithium, and dimethylchlorosilane is 8:1:1; S13: Disperse hexa(4-allylphenoxy)cyclotriphosphazene in toluene, use an isopropanol solution of chloroplatinic acid as a catalyst, heat to 105°C in a nitrogen environment, add single-end active hydrogen polydimethylsiloxane after the system temperature stabilizes, react for 12 hours, cool and remove impurities by reduced pressure distillation to obtain polysiloxane-grafted cyclotriphosphazene; wherein hexa(4-allylphenoxy)cyclotriphosphazene and single-end active hydrogen polydimethylsiloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 6:3; Step 2: 100kg of polyethylene, 18kg of ethylene-vinyl acetate copolymer, 12kg of polyethylene grafted glycidyl methacrylate, 15kg of polysiloxane grafted cyclotriphosphazene, 75kg of magnesium hydroxide and 75kg of calcium carbonate are mixed and melt-blended at 140°C; the melt-blended material is put into a mold, hot-pressed at 135°C and 3.5MPa, and irradiated with a high-energy electron beam at a dose of 170kGy; and a cable waterproof insulation material is obtained.

[0025] Experiment: The performance of the cable waterproof insulation materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 was tested.

[0026] Mechanical properties test: The samples were made into dumbbell-shaped mechanical properties test specimens with a thickness of 2mm and a gauge length of 27mm. Five parallel test specimens were prepared for each test sample. At 25±1℃, the tensile rate of the tensile tester was 120mm / min. The average values ​​were taken as the elongation at break and tensile strength.

[0027] Hydrophobic performance test: Characterized by water contact angle, tested with a 4µL deionized water droplet.

[0028] Flame retardant performance test: characterize using limiting oxygen index.

[0029] Scratch resistance test: The sample is made into a 20cm×20cm×1cm sample plate, and the plastic surface is scratched using an electric cross-hatch instrument in accordance with the standard GMW14688; a 0.5mm scratching head is used to scratch 20 scratches with a spacing of 4mm and a length of 40mm on the sample plate at a speed of 1000mm / min under a pressure of 5N. After scratching in one direction, the plastic plate is rotated 90° and scratched again; a gloss meter is used to compare the change in gloss before and after scratching to determine the scratch resistance of the plastic surface. The smaller the change in gloss before and after scratching, the better the scratch resistance of the plastic surface. △L is used to represent the change in gloss before and after scratching, △L=L1 / L2; where L1 is the gloss before scratching, and L2 is the gloss after scratching.

[0030] The experimental results are shown in Table 1.

[0031] Table 1. Test results of various properties of waterproof insulation materials

[0032] Conclusion: The data of Examples 1 to 3 and Comparative Examples 1 to 3 show that the waterproof insulating material prepared by the present invention has good properties and can be used to prepare the outer protective sheath of cables. The data of Example 1 and Comparative Example 1 show that after adding polysiloxane-grafted cyclotriphosphazene, various properties of the material are improved; the data of Example 2 and Comparative Example 2 show that compared with hexa(4-allylphenoxy)cyclotriphosphazene, polysiloxane-grafted cyclotriphosphazene has better dispersibility in the resin, and the presence of polysiloxane segments improves the mechanical strength (tensile strength and toughness), surface hydrophobicity and wear resistance of the material. During the combustion process, the molten droplet of the organosilicon flame retardant passes through the polymer matrix and transfers to the surface of the substrate to form a dense and stable silicon-containing (mainly silicon dioxide) carbon layer, which prevents the combustible substances decomposed by combustion from escaping, and also plays a role in heat insulation and oxygen isolation, preventing the material from further thermal decomposition, thereby achieving a flame retardant effect; the data of Example 3 and Comparative Example 3 show that too high a polysiloxane grafting amount will affect the cross-linking of polysiloxane-grafted cyclotriphosphazene with the polyethylene substrate, and the material performance is reduced.

[0033] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a waterproof cable insulation material, characterized in that: The following steps are involved: Polyethylene, ethylene-vinyl acetate copolymer, polyethylene grafted glycidyl methacrylate, polysiloxane grafted cyclotriphosphazene, magnesium hydroxide and calcium carbonate are melt-blended; the melt-blended materials are put into a mold, hot-pressed and then irradiated with a high-energy electron beam to obtain a cable waterproof insulation material.

2. The method for preparing a waterproof cable insulation material according to claim 1, characterized in that: The amount of each component, calculated by weight, is 100 parts of polyethylene, 10-25 parts of ethylene-vinyl acetate copolymer, 12-17 parts of polyethylene grafted glycidyl methacrylate, 8-15 parts of polysiloxane grafted cyclotriphosphazene, 50-80 parts of magnesium hydroxide, and 50-80 parts of calcium carbonate.

3. The method for preparing a waterproof cable insulation material according to claim 1, characterized in that: The melt blending temperature is 125~140°C; the hot pressing molding temperature is 125~135°C and the pressure is 3~3.5MPa; the high energy electron beam irradiation dose is 150~170kGy.

4. The method for preparing a waterproof cable insulation material according to claim 1, characterized in that: The preparation method of polysiloxane grafted cyclotriphosphazene is as follows: hexa(4-allylphenoxy)cyclotriphosphazene is dispersed in toluene, an isopropanol solution of chloroplatinic acid is used as a catalyst, the temperature is raised to 100-105°C in a nitrogen environment, and after the system temperature is stabilized, single-terminal active hydrogen polydimethylsiloxane is added, the reaction is carried out for 10-12 hours, and after cooling, impurities are removed by reduced pressure distillation to obtain polysiloxane grafted cyclotriphosphazene.

5. The method for preparing a waterproof cable insulation material according to claim 4, characterized in that: Hexa(4-allylphenoxy)cyclotriphosphazene reacts with single-terminal active hydrogen polydimethylsiloxane at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 6:(1-2).

6. The method for preparing a waterproof cable insulation material according to claim 4, characterized in that: The preparation method of hexa(4-allylphenoxy)cyclotriphosphazene is as follows: 4-allylphenol is dispersed in acetone, magnetically stirred under a nitrogen environment, sodium hydroxide and catalyst tetrabutylammonium bromide are added, the mixture is heated to 40-45°C, reacted for 3-4 hours, and then hexachlorocyclotriphosphazene and acetone are added, reacted at 50-55°C for 60-72 hours, and acetone is removed by rotary evaporation; dichloromethane is added to the crude product, and the product is washed with deionized water and saturated sodium chloride aqueous solution in sequence until the water layer is colorless, and dichloromethane is removed by rotary evaporation, ethanol is added for ultrasonic precipitation, filtered, and recrystallized with hot ethanol to obtain hexa(4-allylphenoxy)cyclotriphosphazene.

7. The method for preparing a waterproof cable insulation material according to claim 6, characterized in that: The reaction was carried out in a molar ratio of 4-allylphenol, sodium hydroxide and hexachlorocyclotriphosphazene of 6:6:

1.

8. The method for preparing a waterproof cable insulation material according to claim 4, characterized in that: The preparation method of single-end active hydrogen polydimethylsiloxane is as follows: hexamethylcyclotrisiloxane is dispersed in toluene, n-butyl lithium is used as an anion initiator, tetrahydrofuran is used as a promoter, polymerization reaction is carried out at 40-50° C. for 6-12 hours, dimethylchlorosilane is added for end-capping, low-boiling substances are removed by filtering and reduced pressure distillation, and single-end active hydrogen polydimethylsiloxane is obtained.

9. The method for preparing a waterproof cable insulation material according to claim 8, characterized in that: The molar ratio of hexamethylcyclotrisiloxane, n-butyl lithium and dimethylchlorosilane is (5~8):1:

1.

10. The cable waterproof insulation material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Synthetic method of PDMS-OH (Polydimethylsiloxane Terminated by Mono-Hydroxypropyl)

    CN107446134A

  • Irradiation-sensitized halogen-free flame retardant and preparation method thereof, and application of irradiation-sensitized halogen-free flame retardant in wires and cables

    CN111303484A

  • Low-gloss high-toughness scratch-resistant polypropylene composite material and preparation method thereof

    CN112876799A

  • Cyclotriphosphazene-based silicon-containing flame retardant as well as preparation method and application thereof

    CN116640168A

  • Flame retardant polymeric compositions containing halogen substituted hexakis-(substituted phenoxy)cyclotriphosphazene

    US4029634A